(untitled) (Journal of Civil Engineering Researchers, 2022)
The aftershocks may weaken or collapse structures that were previously damaged under the main earthquake and have not yet been repaired. In this paper, the seismic performance of an 8-story Steel moment frame structures designed in four types of soil is evaluated under the seismic sequence of earthquake and aftershock. The results showed that the seismic performance of the studied frame under the influence of severe aftershocks can be significantly different from the main earthquake mode alone. For example, in type 1 soil, aftershocks can increase the structure displacement by more than 50% compared to the main earthquake mode alone. It was also found that most aftershocks cause a significant increase in the durable displacement of the roof and in a small number of cases it also reduces it. In addition, the impact of aftershocks on the building damaged by the main earthquake will be much greater than in the case in which the structure under the main earthquake has not suffered much damage.